IMPLEMENTATION OF A BALANCED SCORECARD AS A PERFORMANCE MEASUREMENT TOOL IN A WORKSHOP-BASED MANUFACTURING COMPANY - Simbolon, David Hamonangan; Hardiansyah, Hardiansyah (Jurnal Bisnis dan Manajemen (JBM), 2024)
As business becomes increasingly complex and dynamic, organizations need to develop effective strategies to achieve their goals. One strategic management tool introduced to address this challenge is the Balanced Scorecard (BSC). The primary challenge in applying the BSC lies in designing and implementing balanced and relevant performance measures. This study, employing qualitative research methods, examines the use of the Balanced Scorecard (BSC) as a tool to measure performance in a manufacturing company operating in a workshop-based environment. Through in-depth interviews with stakeholders, including top management, functional managers, employees, and investors, the research uncovers the complexities, requirements, and opportunities associated with implementing the BSC in a workshop environment. The findings highlight the potential of the BSC as an appropriate framework for measuring production, quality, efficiency, and innovation, while also drawing attention to the barriers related to integration with existing management systems, understanding workshop procedures, and adaptation for successful implementation. The results of the study provide critical guidance for decision-makers considering the BSC as a performance measurement tool tailored to meet the needs of the shop floor, with the aim of enhancing operational and strategic performance in manufacturing organizations. Keywords: Balanced Scorecard (BSC), Strategic Management, Performance Measurement Abstrak Organisasi perlu mengembangkan strategi yang efektif untuk mencapai tujuan mereka karena bisnis menjadi semakin kompleks dan dinamis. Salah satu alat manajemen strategis yang diperkenalkan untuk menjawab tantangan ini adalah Balanced Scorecard (BSC). Bagaimana merancang dan mengimplementasikan ukuran kinerja yang seimbang dan relevan merupakan isu utama dalam penerapan BSC. Dengan menggunakan metode penelitian kualitatif, penelitian ini mengkaji penggunaan Balanced Scorecard (BSC) sebagai alat untuk mengukur kinerja pada sebuah perusahaan manufaktur yang beroperasi di lingkungan berbasis workshop. Penelitian ini mengungkap kompleksitas, persyaratan, dan peluang yang terkait dengan penerapan BSC di lingkungan workshop melalui wawancara mendalam dengan para pemangku kepentingan, termasuk manajemen puncak, manajer fungsional, karyawan, dan investor. Hasilnya menggarisbawahi potensi BSC sebagai kerangka kerja yang tepat untuk mengukur produksi, kualitas, efisiensi, dan inovasi, tetapi juga menarik perhatian pada hambatan integrasi dengan sistem manajemen saat ini, pemahaman tentang prosedur workshop, dan adaptasi untuk implementasi yang sukses. Hasil penelitian ini memberikan panduan penting bagi para pengambil keputusan untuk mempertimbangkan penggunaan BSC sebagai alat pengukuran kinerja yang memenuhi kebutuhan lantai pabrik dengan tujuan untuk meningkatkan kinerja operasional dan strategis dalam organisasi manufaktur. Kata Kunci : Balanced Scorecard (BSC), manajemen strategis, pengukuran kinerja